2008
DOI: 10.1111/j.1741-3737.2008.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Single, Cohabitating, and Married Mothers’ Time With Children

Abstract: Utilizing the 2003 and 2004 American Time Use Survey (ATUS), this study examines the relationship between family structure and maternal time with children among 4,309 married mothers and 1,821 single mothers with children less than 13 years of age. Single mothers spend less time with their children than married mothers, though the differences are not large. Marital status and living arrangement differences in time with children largely disappear or single mothers engage in more child care than married mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
123
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(133 citation statements)
references
References 28 publications
6
123
1
3
Order By: Relevance
“…There were no significant differences (see Table 1) between the groups. This finding is supported by previous studies in which it is suggested that there are no significant differences between single and married mothers (Avison et al, 2007;Greitemeyer, 2009;Kendig & Bianchi, 2008). The results of this study suggest that regardless of marital status, children perceived their mothers to be more autonomy-supportive and less psychologically controlling.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…There were no significant differences (see Table 1) between the groups. This finding is supported by previous studies in which it is suggested that there are no significant differences between single and married mothers (Avison et al, 2007;Greitemeyer, 2009;Kendig & Bianchi, 2008). The results of this study suggest that regardless of marital status, children perceived their mothers to be more autonomy-supportive and less psychologically controlling.…”
Section: Resultssupporting
confidence: 81%
“…For instance, single and married mothers have similar personality characteristics, overall psychological well-being, and are similarly vulnerable and reactive to stressors (Avison, Ali, & Walters, 2007;Greitemeyer, 2009). Kendig and Bianchi (2008) found that single mothers do not spend significantly less time with their children than do married mothers. If they do spend less time with their children then this is purely because of their social structural location.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This is true on account that many single mothers faced stress and emotional disturbance from the dual role playing in the family (Kendig & Bianchi, 2008). The time deficit to take care of the children in addition to low emotional support from the community, contributed greatly to the well-being of single mothers (Smith, 1980).…”
Section: Relationship Between Demographic Factors On the Belief Systementioning
confidence: 99%
“…Active care was also different for children in single parent families compared to two-parent families in this study (24 hours per week for single parents compared to 31 hours per week for twoparent families). Kendig and Bianchi (2008) also conclude that single mothers spend less time with their children than married mothers mostly because of social structural disadvantages (Kendig & Bianchi, 2008 …”
Section: Marital Status and Time Spent With Childrenmentioning
confidence: 99%